Regime jurídico dos fundos de investimento - Mário Tavernard Martins de Carvalho (2012)
This paper discusses the legal regime for investment trusts in Brazil. Before discussing the issue properly, it was necessary to contextualize it according to its economic purpose, inserting it into the capital market. Thus, it was possible to understand the characteristics of the institute, comparing the rules of regulatory agencies, especially Instruction 409 issued by the Comissão de Valores Mobiliários, and related legislation. It was possible to identify the essence of company in the investment trusts, and expose and comment on the specifics of the existing relationships. Due to practical demands, aimed to draw parallels, comment applicability and analyze use of typical institutes of corporate law in investment trusts. More than answer questions, this research tried to raise them, to provide a comprehensive understanding, althought we recognize it is a very dynamic institute and in permanent construction.